ACUTE TOXICITY AND HEPATO-RENAL PROTECTION OF LIME JUICE, HONEY AND THEIR FLAVONOID-RICH FRACTIONS IN HIGH FAT-DIET INDUCED OBESE RAT MODEL - Alexander, Idoko; Elijah, Parker Joshua; Uzoma, Njoku Obioma; Ifeanyi, Ejike David; Victor, Egbuji Jude; Patrick O, Ugwudike; Chioma, Jennifer Ndubuisi (Universal Journal of Pharmaceutical Research, 2024)
Introduction: A major consideration for the use of alternative herbal medicine from natural compounds is the concern of safety due to possible toxicity. This study evaluated the safety and hepato-renal protection of fresh lime juice (FLJ), raw honey (RH) and their flavonoid-rich fractions in obese rat induced high fat-diet (HFD). Methods: Oral acute toxicity (LD50) study involved 24 female Wistar rats, divided into 8 groups of 3 rats, administered 300 mg/kg and 2000 mg/kg of FLJ, RH, methanol flavonoid rich fraction of lime juice (MFLJ) and ethyl acetate flavonoid rich fraction of honey (EAFH) respectively, for 14 days. Simultaneously, for the anti-obesity study, 24 neonate Wistar rats of 21-days old, divided into 2 groups of 12 rats (for obesity induction phase-1, for two weeks), and regrouped into 4 groups of 4 rats (14 days treatment phase-2), were used. Results: Result of LD50 on FLJ, RH, MFLJ, and EAFH showed no toxicity, no motility, and body weight of rats was not adversely affected evenup to 2000 mg/kg.The increased body weight of the HFD-obese rats was significantly (p<0.05)reduced compared to control. There was significant (p<0.05) decrease in activities of aspartate aminotransferase and alanine aminotransferase after MIX, MFLJ and EAFH administration, compared with control. Also, total protein and bilirubin concentrations was not significantly (p<0.05) different compared to control. Administration of EAFH significantly (p<0.05) reduced the concentrations of creatinine, urea, potassium, and chloride; while MIX and EAFH significantly (p<0.05) increased their concentrations compared to control. Conclusion: It may be concluded that FLJ, RH, MFLJ, and EAFH are safe for consumption and also possess liver and renal protection. Peer Review History: Received: 2 October 2023; Revised: 9 November; Accepted: 27 December; Available online: 15 January 2024 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Dr. Gehan Fawzy Abdel Raoof Kandeel, Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com